(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
This article talks about the role of national cultural centers in Uzbekistan in interethnic harmony. The author, relying on scientific data, studied and analyzed the specific aspects of the role of national cultural centers in Uzbekistan in interethnic harmony based on available literature.